Financial Market of Kazakhstan: Current State and Ways of Stabilization in the Context of Global Instability - LUKHMANOVA, Gulnar Koishybaevna; BAISHOLANOVA, Karlygash Sovetovna; BAIBULEKOVA, Lyailya Abdybayevna; PRIMZHAROVA, Kalyash Kuanyshevna; KASSYMBEKOVA, Gulzhakhan Ryskulovna (Journal of Advanced Research in Law and Economics, 2019)
The financial market belongs to the segment of the economic system, which is especially strictly regulated and controlled by state bodies. The special emphasis of the state on the issues of control and supervision of the financial market is due to the fact that the degree of development of its infrastructure has direct impact on the economic situation of the country. The conducted analysis of the financial market development covers the period from 2014 through 2017. The article reflects the features of the financial market of Kazakhstan and its role for the national economy, as well as the mechanism of state regulation of the financial market. The authors reveal the problems of the financial market functioning at the present stage, and draw conclusion about the need to develop the regulatory infrastructure of the financial market to achieve sustainable economic growth.